2017
DOI: 10.1002/14651858.cd011457.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis for acute kidney injury

Abstract: Based on moderate (mortality, recovery of kidney function), low (infectious complications), or very low certainty evidence (correction of acidosis) there is probably little or no difference between PD and extracorporeal therapy for treating AKI. Fluid removal (low certainty) and weekly delivered Kt/V (very low certainty) may be higher with extracorporeal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 38 publications
0
33
0
3
Order By: Relevance
“…[7][8][9][10] With the expanded PD-use, The International Society for Peritoneal Dialysis (ISPD) developed guidelines for the use of PD to treat patients with AKI. 3 The recommendation that PD was an acceptable form of RRT for AKI in these guidelines was supported by two meta-analyses (including a Cochrane analysis) both of which concluded that PD is not inferior to extracorporeal therapies in the management of patients with AKI 11,12 .…”
Section: Advantagesmentioning
confidence: 99%
“…[7][8][9][10] With the expanded PD-use, The International Society for Peritoneal Dialysis (ISPD) developed guidelines for the use of PD to treat patients with AKI. 3 The recommendation that PD was an acceptable form of RRT for AKI in these guidelines was supported by two meta-analyses (including a Cochrane analysis) both of which concluded that PD is not inferior to extracorporeal therapies in the management of patients with AKI 11,12 .…”
Section: Advantagesmentioning
confidence: 99%
“…The efficacy of PD in the management of AKI is at least as efficient as hemodialysis (HD) and possibly as efficient as hemodiafiltration [ 17 , 18 ]. Currently, the best evidence is found in a meta-analysis from Liu et al [ 19 ] (analysis of 6 studies with 484 patients), where PD therapy and extracorporeal RRT are compared for management of AKI. In this study, PD therapy has little or no difference with other extracorporeal therapies concerning all-cause mortality and recovery of kidney function (Moderate level of evidence).…”
Section: Efficacy Of Peritoneal Dialysis In the Management Of Akimentioning
confidence: 99%
“…On the other hand, PD may be slightly less effective in the removal of ultrafiltration volume (low level of evidence) and has no difference for infectious complications (low level of evidence). The efficacy of the correction of acidosis or Kt/V dosage may be higher in extracorporeal therapies; however, the evidence for this argument is very low [ 19 ].…”
Section: Efficacy Of Peritoneal Dialysis In the Management Of Akimentioning
confidence: 99%
See 1 more Smart Citation
“…Eine neuere Studie aus Brasilien fand keinen Unterschied im Outcome zwischen high-volume-Peritonealdialyse und verlängerter täglicher Hämodialyse [38]. Eine Meta-Analyse von 6 Studien mit 484 Patienten fand ebenfalls keine Unterlegenheit der Peritoenaldialyse gegenüber extrakorporalen Nierenersatzverfahren [39]. Expertise und Verfügbarkeit lassen dieses Verfahren jedoch zur Ausnahme auf den Intensivstationen in Deutschland werden.…”
Section: Ihd Cvvh Sled Pd -Nierenersatzverfahren Bei Akuter Nierenunclassified